The influence of time of day on the performance of adolescent swimmers. (3rd August 2021) - Nunes, Rodolfo Soares Mendes; Freitas, Ana Flávia Lopes; Vieira, Elaine
ABSTRACT: The study aimed to investigate the eﬀects of time-of-day, chronotype, and sex differences on the relationships between anxiety, depression, sleep quality, and swimming performance of normally diurnally active adolescent athletes. Thirty-three competitive swimmers, 20 boys (14.8 ± 1.60 y) and 13 girls (14.4 ± 1.51 y) from two different swimming centers participate in the study. They performed 50 m and 400 m front crawl trials twice, at 08:00 h and 18:00 h, with an interval of 48 h in a 50 m swimming pool. Chronotype, depression, anxiety levels, and sleep quality were accessed by questionnaires. No effect of time-of-day was observed in girls for the 50 and 400 m trials. The swimming performance of boys was similar in the 50 m trials independent of time-of-day, but in the 400 m trial the performance time was better in the evening compared to morning. The best evening performance was observed among N-types. Linear regression analysis of the data of all participants revealed a positive correlation between sleep quality and anxiety level ( p = .016; R 2 = 0.1769) and sleep quality and depression level ( p = .006; R 2 = 0.2192). There was no correlation between chronotype and sleep quality in either sex ( p = .4044; R 2 = 0.0232). We conclude that time-of-day can influence the performance of adolescent swimmers that differs with the distance of the trial and by sex. We also demonstrated the importance of sleep quality among adolescents swimmers as a factor that can influence anxiety and depression and thus consequently affect their performance.